JUSTICE AND LIBERTY IN HEGEL - Thadeu Weber (Ethic@: an International Journal for Moral Philosophy)
This paper aims to make explicit the concept of justice in Hegel’s Philosophy of Right. It bounds it to the idea of liberty in its different ways of determination. It starts from the notion of person of right and indicates the fundamental rights that derive from the expression of this legal capacity. It highlights the right of necessity as a right to make an exception in favor of itself aiming the actualization of justice. It shows how, through the Law, in civil society, it happens the administration of justice.